352 Longitudinal Infusion of Insulin-Like Growth Factor-I and Igf-Binding Protein-3 Complex to Five Preterm Infants - Pharmacokinetics and Short Term Safety. (October 2012) - Ley, D; HansenPupp, I; Niklasson, A; Domellöf, M; Friberg, L; Borg, J; Löfquist, C; Hellgren, G; Smith, L; Hård, AL; Hellström, A
Abstract : Introduction: In preterm infants, low levels of insulin like growth factor-I (IGF-I) and IGF binding protein 3 (IGFBP-3) are associated with impaired brain growth and retinopathy of prematurity (ROP). Treatment with IGF-I/IGFBP-3 may be beneficial for brain development and decrease the prevalence of ROP. Methods: In a phase II pharmacokinetic and safety study, five infants (3 girls) with a median (range) gestational age (GA) of 26+6 (26+0 – 27+2) weeks and birth weight (BW) of 990 (900–1212) g received continuous intravenous infusion of rhIGF-I/rhIGFBP-3. Treatment was initiated during the first postnatal day and continued for a median (range) duration of 168 h (47–168) in doses between 21–111 µg/kg/24h. Results: Treatment with rhIGF-I/rhIGFBP-3 was associated with higher serum IGF-I and IGFBP-3 concentrations (p<0.001) than model-predicted endogenous levels. Out of 74 IGF-I samples measured during study drug infusion, 37 (50%) were within target range, 4 (5%) above and 33 (45%) were below. Predicted dose of rhIGF-I/rhIGFBP-3 to establish circulating levels of IGF-I within the intrauterine range in a 1000 g infant was 75–100 µg/kg/24 h. No hypoglycemia or other adverse effects were recorded. Discussion: Continuous intravenous infusion of rhIGF-I/rhIGFBP-3 was effective in increasing serum concentrations of IGF-I and IGFBP-3. Administration under study conditions was safe.